Comparing physician associates and foundation year two doctors-in-training undertaking emergency medicine consultations in England: a mixed-methods study of processes and outcomes. Issue 9 (1st September 2020) - Halter, Mary; Drennan, Vari; Wang, Chao; Wheeler, Carly; Gage, Heather; Nice, Laura; de Lusignan, Simon; Gabe, Jonathan; Brearley, Sally; Ennis, James; Begg, Phil; Parle, Jim
Abstract : Objectives: To compare the contribution of physician associates to the processes and outcomes of emergency medicine consultations with that of foundation year two doctors-in-training. Design: Mixed-methods study: retrospective chart review using 4 months' anonymised clinical record data of all patients seen by physician associates or foundation year two doctors-in-training in 2016; review of a subsample of 40 records for clinical adequacy; semi-structured interviews with staff and patients; observations of physician associates. Setting: Three emergency departments in England. Participants: The records of 8816 patients attended by 6 physician associates and 40 foundation year two doctors-in-training; of these n=3197 had the primary outcome recorded (n=1129 physician associates, n=2068 doctor); 14 clinicians and managers and 6 patients or relatives for interview; 5 physician associates for observation. Primary and secondary outcome measures: The primary outcome was unplanned re-attendance at the same emergency department within 7 days. Secondary outcomes: consultation processes, clinical adequacy of care, and staff and patient experience. Results: Re-attendances within 7 days (n=194 (6.1%)) showed no difference between physician associates and foundation year two doctors-in-training (OR 0.87, 95% CI 0.61 to 1.24, p=0.437). If seen by a physician associate, patients were more likely receive an X-ray investigation (OR 2.10, 95% CI 1.72 to 4.24), p<0.001), after adjustment for patient characteristics, triage severity of condition and statistically significant clinician intraclass correlation. Clinical reviewers found almost all patients' charts clinically adequate. Physician associates were evaluated as assessing patients in a similar way to foundation year two doctors-in-training and providing continuity in the team. Patients were positive about the care they had received from a physician associate, but had poor understanding of the role. Conclusions: Physician associates in emergency departments in England treated patients with a range of conditions safely, and at a similar level to foundation year two doctors-in-training, providing clinical operational efficiencies.